Promosi dan Marketing Madrasah Ibtidaiyah Negeri Berbasis Digital - Wardi, Moh; Susantin, Herlin; Fadli Wahyudi, Heri (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2024)
This study aims to explain the madrasah marketing strategy by utilizing social media at MIN 2 Sumenep in increasing the number of new student applicants. Then to analyse the contribution of social media-based educational marketing strategies in increasing the number of registrants and describe the supporting factors and obstacles in implementing educational marketing strategies based on the use of social media. The method used is a qualitative method with the main focus on the marketing strategy of the education programme to improve the image of the MIN 2 Sumenep institution. The data collection techniques used include interviews with the madrasah head, deputy head and teachers, as well as observation and documentation. Data were analysed using the Miles and Huberman model which includes three stages: data reduction, data display and conclusion drawing. The conclusion of this study is that the digital marketing strategy through social media implemented at MIN 2 Sumenep, including the use of websites, Facebook, Instagram, YouTube and TikTok, has successfully increased the number of new student registrations. The marketing is done effectively by involving madrasah stakeholders, providing a strong identity and improving the quality of education services. Although not yet optimal, the contribution of this strategy is very significant in attracting the attention and interest of prospective students. Sustainability and consistent management are needed for better results.